Detection of antigens and antibodies in the urine of humans with Plasmodium falciparum malaria. - Rodriguez-del Valle, M (1991)
Humans infected with Plasmodium falciparum frequently have elevated levels of proteins in their urine, but it is unclear if any of these proteins are parasite antigens or antimalarial antibodies. To resolve this question, urine samples from malaria patients and controls living in Thailand and Ghana were evaluated. Urine samples from 85% of the patients had elevated protein levels and contained proteins with Mrs ranging from less than 29,000 to greater than 224,000 as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Antisera were produced against urine from infected and control subjects. Antisera raised against infected, but not control, urine were positive by indirect immunofluorescence on P. falciparum parasites and immunoprecipitated approximately 12 unique bands from extracts of parasites metabolically labeled with 35S-methionine. These data suggest that a variety of P. falciparum antigens are released into urine during acute infection. It is also likely that anti-P. falciparum antibodies are present in the urine of malaria patients because samples from these patients, but not controls, were positive in indirect immunofluorescence assays and immunoprecipitated at least 19 P. falciparum antigens from extracts of metabolically labeled parasites. The detection of malarial antigens and antibodies in urine may lead to a new approach for the diagnosis of malaria.